2021
DOI: 10.18332/ejm/140459
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of antenatal care services and its sociodemographic correlates in urban and rural areas in Delhi, India

Abstract: INTRODUCTION Timely and quality antenatal care (ANC) is an essential element of universal health coverage and a key determinant for the prevention of maternal mortality. Nevertheless, evidence from large-scale health surveys in developing countries highlight a lack of access and utilization of antenatal care especially among socioeconomically disadvantaged populations. METHODS A total of 200 women were recruited from urban and rural primary care service provision areas of a government medical college in Delhi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
(11 reference statements)
1
11
1
Order By: Relevance
“…Ogbo et.al 2019 also found that the enablers of the recommended ANC visits are higher household wealth status and parental education, residence in Southern India but, residence in East and Central India were barriers to appropriate ANC service use [24] . Further, this study highlights that younger women are less likely to receive the adequate quality ANC and it decreases with an increase in the parity of women but increases if the mother has experienced adverse pregnancy outcomes previously, which is very much similar to the wellestablished associations found in other studies on utilisation of ANC [9,[25][26] . Studies in context of neighbouring countries, like Nepal, also supports the ndings of this study [27] .…”
Section: Interpretations Of Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…Ogbo et.al 2019 also found that the enablers of the recommended ANC visits are higher household wealth status and parental education, residence in Southern India but, residence in East and Central India were barriers to appropriate ANC service use [24] . Further, this study highlights that younger women are less likely to receive the adequate quality ANC and it decreases with an increase in the parity of women but increases if the mother has experienced adverse pregnancy outcomes previously, which is very much similar to the wellestablished associations found in other studies on utilisation of ANC [9,[25][26] . Studies in context of neighbouring countries, like Nepal, also supports the ndings of this study [27] .…”
Section: Interpretations Of Findingssupporting
confidence: 85%
“…The coverage of antenatal care services largely depends on various socio-demographic factors, and are signi cantly associated with women's empowerment, maternal education, maternal health status, birth order, economic status, and availability of health facilities [9][10] . There are many studies on the associated factors of low utilization of ANC in different parts of India but the literature shows that attempts to understand the factors associated with the utilization of quality ANC in India and even in lowand middle-income countries are very rare [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Access to high-quality maternal health care before, during, and after childbirth has been identified as an effective way of reducing preventable maternal deaths [ 3 , 9 , 10 ]. Antenatal care (ANC) provides a crucial opportunity for skilled healthcare professionals to address potential health risks during pregnancy through disease prevention, identification, and management [ 11 , 12 ]. ANC also allows providers to engage pregnant women in both immediate and long-term health promotion and education [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this finding was slightly higher than the results of the studies done in Tigray, Northern Ethiopia (50.1%) [ 17 ], and Egypt (51.3%) [ 30 ]. Moreover, this finding was greatly higher than the level of noncompliance to recommended ANC reported in the studies done in Ghana (15.2%) [ 20 ], Ethiopia (36.3%) [ 11 ], Malaysia (37%) [ 34 ], Zambia (40%) [ 28 ], Sub-Saharan Africa (41.5%) [ 10 ], Myanmar (42%) [ 35 ], East African (43.6%) [ 9 ], and India (47%) [ 36 ]. On the contrary, the level of nonadherence to the recommended ANC visits in this study was lower than that reported in the studies done in Ethiopia (63.4%) [ 12 ], Bangladesh (68.7%) [ 29 ], Rwanda (86.6%) [ 37 ], and Sub-Saharan Africa (92.3%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%